Analysis of All factors Against Food and Beverages (F&B) MSME’s Business Turnover in Surabaya: during COVID-19 - Rinarta, Chikara Dini (MediaTrend, 2024)
Surabaya and other cities in East Java played a significant role for economic development during the expansion of COVID-19 in 2020, most of MSME productivity in Indonesia was dramatically decreased. Nevertheless, Surabaya city had 30% increased MSME productivity from the end of 2020. This research aims to examine the factors of increased or decreased turnover of FB (Food and Beverages) MSMEs during the COVID-19 pandemic, so that the results of this research can be a survival strategy for MSMEs, especially during the pandemic. The research data was collected through an interview process with 110 food and beverage MSME who are from Surabaya City (as scope as members of Surabaya Kriya Gallery). After that, MSMEs will be grouped into MSMEs according to how increased or decreased turnover they got. Based on this, firstly, we collect the survey of 110 owners as a sample, with Lemeshow sampling; Second, analyze data with binary logistic regression; Then, analyze the influence of the COVID-19 pandemic situation on the MSMEs turnover. It can be revealed that all independent variables (business training, gender, location, and marketing) affect their turnover but statistically only location has a strong effect on turnover. Business location has been supported by marketing.